2012
DOI: 10.7150/jca.4919
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free Circulating miRNA Biomarkers in Cancer

Abstract: Considerable attention and an enormous amount of resources have been dedicated to cancer biomarker discovery and validation. However, there are still a limited number of useful biomarkers available for clinical use. An ideal biomarker should be easily assayed with minimally invasive medical procedures but possess high sensitivity and specificity. Commonly used circulating biomarkers are proteins in serum, most of which require labor-intensive analysis hindered by low sensitivity in early tumor detection. Since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
122
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(130 citation statements)
references
References 183 publications
(243 reference statements)
5
122
1
2
Order By: Relevance
“…In line with our findings, a recent study [19] showed that 3 serum miRNAs, including let-7f, could separate HBV-HCC cases from controls. MiR-122, the most abundant liver-specific miRNA, is considered a suppressor of cell proliferation and malignant transformation of hepatocytes with remarkable tumor inhibition activity [32][33][34]. Interestingly, although downregulation of miR-122 was frequently reported in the HCC tumor tissues [2,34,35], Qi et al [36] showed that miR-122 in serum was elevated in HCC patients and markedly reduced in post-operative serum samples, which is consistent with the observation in our study.…”
Section: Discussionsupporting
confidence: 81%
“…In line with our findings, a recent study [19] showed that 3 serum miRNAs, including let-7f, could separate HBV-HCC cases from controls. MiR-122, the most abundant liver-specific miRNA, is considered a suppressor of cell proliferation and malignant transformation of hepatocytes with remarkable tumor inhibition activity [32][33][34]. Interestingly, although downregulation of miR-122 was frequently reported in the HCC tumor tissues [2,34,35], Qi et al [36] showed that miR-122 in serum was elevated in HCC patients and markedly reduced in post-operative serum samples, which is consistent with the observation in our study.…”
Section: Discussionsupporting
confidence: 81%
“…47 Hence, these highly expressed BART microRNAs may serve as another mechanistic biomarker for NPC recognition. A few studies have reported detection of BART microRNAs in sera or plasma from NPC patients, but only included small numbers of samples from NPC patients and lacked information on the source of these BART microRNAs (39)(40)(41). It is possible that some of the BART microRNAs detected in sera or plasma in these studies may also have come from apoptotic or circulating cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…SMAD4 overexpression could rescue the promoting effects of miR-574-3p on cancer cell growth, which additionally supports the theory that miR-574-3p may be associated with SMAD4. miRNAs are critical regulators and biomarkers for numerous types of cancers (8,(21)(22)(23)(24). There are several miRNAs that have been found to be abnormal in human osteosarcoma, including miR-141, miR-429, miR-451, miR-195, miR-183 miR-199a-3p, miR-127-3p and miR-376c (3,5,10,(25)(26)(27).…”
Section: Downregulation Of Mir-574-3p Inhibited Cell Growth and Inducmentioning
confidence: 99%
“…MicroRNA (miRNA) is a class of small non-coding RNA, with lengths of 18-22 nucleotides; they play important roles in numerous biological processes through transcriptional suppression of target genes (6)(7)(8). The critical functions of numerous miRNAs in cancer biology have been illustrated, including the regulation of various cellular processes, such as proliferation and apoptosis (3,5,9,10).…”
Section: Introductionmentioning
confidence: 99%